Micra pacemaker implant after cardiac implantable electronic device extraction: feasibility and long-term outcomes. Issue 8 (10th June 2019) - Zucchelli, Giulio; Barletta, Valentina; Della Tommasina, Veronica; Viani, Stefano; Parollo, Matteo; Mazzocchetti, Lorenzo; Cellamaro, Tea; Paperini, Luca; Di Cori, Andrea; De Lucia, Raffaele; Segreti, Luca; Soldati, Ezio; et al.
Abstract: Aims: We aimed at investigating the feasibility and outcome of Micra implant in patients who have previously undergone transvenous lead extraction (TLE), in comparison to naïve patients implanted with the same device. Methods and results: Eighty-three patients (65 males, 78.31%; 77.27 ± 9.96 years) underwent Micra implant at our centre. The entire cohort was divided between 'post-extraction' (Group 1) and naïve patients (Group 2). In 23 of 83 patients (20 males, 86.96%; 73.83 ± 10.29 years), Micra was implanted after TLE. Indication to TLE was an infection in 15 patients (65.21%), leads malfunction in four (17.39%), superior vena cava syndrome in three (13.05%), and severe tricuspid regurgitation in one case (4.35%). The implant procedure was successful in all patients and no device-related events occurred at follow-up (median: 18 months; interquartile range: 1–24). No differences were observed between groups in fluoroscopy time (13.88 ± 10.98 min vs. 13.15 ± 6.64 min, P  = 0.45), single device delivery (Group 1 vs. Group 2: 69.56% vs. 55%, P  = 0.22), electrical performance at implant and at 12-month follow-up (Group 1 vs. Group 2: pacing threshold 0.48 ± 0.05 V/0.24 ms vs. 0.56 ± 0.25 V/0.24 ms, P  = 0.70; impedance 640 ± 148.83 Ohm vs. 583.43 ± 99.7 Ohm, P  = 0.27; and R wave amplitude 10.33 ± 2.88 mV vs. 12.62 ± 5.31 mV, P  = 0.40). A non-apical site of implant was achievable in the majority of cases (72.3%) without differences among groups (78.26% vs. 70%; P  = 0.42). Conclusion: Micra implant is an effective and safe procedure in patients still requiring a ventricular pacing after TLE, with similar electrical performance and outcome compared with naïve patients at long-term follow-up.